On the genus Israelaphis Essig in Sicily, with description of a new species (Rhynchota-Homoptera Aphidoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two aphid species belonging to genus lsraelaphis Essig were collectedfor the first time in Sicily (Italy) during the years 1998-99. One of the two aphidsis described as a new taxon, /. ilharcoi sp.n., the other one being the well knowntype-species /. carmini. Both species are recorded for Israel , Portugal and Sicily,where they live on annual grasses belonging to the genera Bromus, Avena,Hordeum. Notes are given on their life-cycle and taxonomy. A key to apterousviviparous morphs allows the identification of the four aphid species which areknown up to now to belong to the genus.
Keywords: aphids; Israelaphis; Israelaphidinae; taxonomy; Sicily; Italy